The Five-Year Outcomes of Breast Cancer Surgical Management at the Colentina Surgical Clinic, Bucharest, Romania: A Descriptive Retrospective Analysis Between 2019 and 2023 - Cristian Botezatu; Daniel-Ovidiu Costea; Martina Nichilò; Angela Madalina Lazar; Dan Andraș; Mircea-Ion Radu; Bogdan Mastalier (Life)
Background: Breast cancer still represents the most commonly diagnosed cancer among women, accounting for 12.5% of all new annual cancer cases worldwide. In Romania in 2020, breast cancer was the most common, with a share of new cases of 26.9%, far behind the rates of colon cancer (11.8%) and cervix cancer (7.5%). The aim of this study is to reveal five years of experience in treating breast cancer at the Surgical Clinic of the Colentina Hospital in Bucharest, Romania. Methods: Retrospective analysis, including 68 patients admitted to our clinic between January 2019 and December 2023 undergoing modified radical mastectomy, sectorectomy, or subcutaneous mastectomy. Results: Madden-modified radical mastectomy with total excision of the axillary lymph nodes accounted for 77.94% of surgeries, with a complication rate of 13.2%, represented by lymphedema of the ipsilateral arm and prepectoral seroma. Conclusions: Continuous innovation regarding early diagnosis and treatment methods in our surgical clinic will, hopefully, contribute to improving the outcomes of our patients.